Project Citizen Model as Character Education Strengthening - Sulistyarini Sulistyarini; Tri Utami; Hasmika Hasmika (STKIP Singkawang, 2019)
This study aims to see the effectiveness of the use of the Project Citizen model as strengthening character education in the learning of Pancasila and Citizenship Education. This research is the experimental research. The model is applied to parallel class XII in State Senior High School (SMAN) 8 Pontianak. Class XII IPS 1 and class XII IPS3. Students of class XII IPS 1 were treated by learning the Project Citizen model and class XII IPS 3 by learning ordinary classical models (the teacher used the lecture and question and answer method). Character values seen are religious, independent, cooperation, integrity, and nationalist values. Based on the results of the t-test on the Expansion class and the Control class, the value of t sig (2-tailed) of 0.000 is smaller than 0.05 so that Ho is rejected. It means that there is a significant difference in strengthening character education in the experimental class using a project citizen model with control who use ordinary learning and effect size. From this study, it is known that the impact of enhancing character education in the XII IPS class of SMAN 8 Pontianak is equal to 1 in the high category, thus learning with the Project citizen model is effective as a reinforcement of character education.